Loss and recovery of carbon and nitrogen after mangrove clearing - Adame, Maria Fernanda; Zakaria, Rozainah Mohamad; Fry, Brian D.; Chong, Ving Ching; Then, Amy Yee Hui; Brown, C.J.; Lee, Shing Yip (Elsevier, 2018)
Offsetting carbon (C) emissions and reducing nitrogen (N) pollution have been goals of mangrove restoration programs around the world. There is a common, yet dubious expectation that mangrove restoration will result in immediate and perpetual delivery of ecosystem services. There are expected time lags between mangrove clearing and C and N losses, and between restoration and C and N gains. Obtaining accurate rates of losses and gains requires frequent and long-term sampling, which is expensive and time consuming. To address this knowledge gap, we used a chronosequence of mangrove forests in mangroves in Matang Mangrove Forest Reserve (MMFR) in Malaysia, a region with one of the most C dense forests in the world. In this site, we assessed the ecosystem C and N stocks, including soil, downed wood, downed litter, and trees. The objective was to measure C and N changes through time. After mangrove clearing, C and N losses in soil and downed wood were rapid, with stocks halved after just one year. In the first 10 years after replantation, the forest recovered quickly, with rates of C accumulation of 9.5 Mg C ha−1 yr−1. After ten years, the rate of accumulation decreased to 2.8 Mg C ha−1 yr−1. However, 40 years after replantation, mangroves were still about 26% lower in C and 15% lower in N compared to our reference forest. The trajectory of recovery of C and N stocks in these forests was different among mangrove components: forest litter recovered rapidly, but downed wood and soil recovered much slower. Programs aimed at reducing C emissions and N pollution should consider that there are temporal lags and ecosystem trade-offs when assessing the effectiveness of mangrove protection and restoration as climate change mitigation strategies.